RAWA Jawura : Legenda dari Jawa Barat / diceritakan kembali oleh A.M. Rustandie & Rahmat Noormansyah; ilustrasi, Rio Purbaya & Mardhani - Rustandie, A.M; Noormansyah, Rahmat; Purbaya, Rio; Mardhani (Pionir Jaya, 1988)
50 hlm : ilus ; 21 cm